Antioxidant and antihypoxic activity of human cord blood extracts obtained with various temperature regimens of destruction of cellular elements and extraction media - Shcheniavskyi, Ivan; Akhatova, Yuliya (Problems of Cryobiology and Cryomedicine, 2025)
The research analysed the dependence of antioxidant and antihypoxic activity of human cord blood (HCB) extracts on the temperature regimen of destruction, salt composition and pH of the extraction solution. Using the adrenaline autooxidation model, it was found that the antiradical activity of all the cryoextracts exceeded this index of those obtained using the same extraction solutions in combination with incubation at 70 ºС for 30 min, or with the use of hypotonic lysis. The content of malondialdehyde and lipid hydroperoxides in the brain of animals exposed to normobaric hypoxia, which were injected with a low-molecular fraction (up to 10 kDa) isolated from HCB cryoextracts, was found to be significantly lower than when being injected with a low-molecular fraction of extracts obtained using high temperature or hypotonic lysis. During hypotonic lysis, enzyme molecules and low-molecular biologically active peptides also undergo significant destructive effects of endogenous proteases and lose their specific activity. It has been proven that cryoextraction, regardless of the applied freeze-thawing rates and the composition and pH of the medium, allows obtaining final products with significantly higher antiradical and anti-hypoxic properties than after holding at high temperature and hypotonic lysis. Our findings prove the prospects of using cryotechnologies in the processing animal and human tissues and blood to obtain raw materials enriched with biologically active substances to produce medicines. Probl Cryobiol Cryomed. 2025; 35(2): 85–91